The Mesoamerican mantises of the genus Phasmomantis Saussure, 1869 (Mantidae: Stagmomantinae: Stagmomantini) - Luna, Manuel De; Hernández-Baltazar, Erick; Cubillos-Macías, Iker; Cuéllar-Rodríguez, Gerardo; Hinojosa-Díaz, Ismael A. (Zootaxa, 2026)
The type material of the two species of the genus Phasmomantis Saussure, 1869 (Mantidae: Stagmomantinae: Stagmomantini) is revisited and illustrated. Phasmomantis sumichrasti (Saussure, 1861) is newly recorded for the Mexican states of Campeche, Chiapas, Nayarit, Puebla, Quintana Roo, San Luis Potosí, Tabasco and Tamaulipas and is confirmed for the country of Honduras via the examination of specimens in scientific collections; it is newly recorded for the Mexican state of Queretaro and confirmed for the country of Nicaragua via the revision of online records in the citizen science platform iNaturalist. The male of Phasmomantis championi Saussure and Zehntner, 1894 is illustrated for the first time. A key for the species, which contemplates both sexes, is proposed.